STATISTICAL EVALUATION OF SURFACE WIND METHOD FOR ELECTRIFICATION IN KEBBI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Africa and Nigeria in particular is blessed with abundant and constant supplies of fine, clean and sustainable mean for rural and urban electricity generation (renewable energy). Renewable energy such as solar, Hydro, Geothermal, Biomass and surface wind etc., has been found very useful in power generation to many sub-Saharan African countries with attendant significant sustainability and reliability. This study was aimed at evaluating and assessing the potentiality of surface wind in Kebbi state for possible power generation thereby mitigating the challenge of energy crisis and demands for rapidly growing population. The suitable model used for the data analysis was ARIMA (1,1,2), and statistics were checked and stationarity of the data were observed and test using Kwiatkowski Phillips, Schmidt and Shin (KPSS) test. The study area from the analysis of surface wind at 0.01%, 0.05% & 0.1% level of significances depicts well for reliability and sustainability for electricity generation in the state. The study found that surface wind due to its abundance in significant amount throughout the year all over the state with highest recorded values obtained in 2009, 2010 and 2011, if well-harnesses and utilizes it could serve as a good prospect for power generation in Kebbi state and its environs.
Keywords: ARIMA model, Evaluation, Renewable energy, Statistics & Surface wind